Tomato seeds vigor under water or salt stress - Silva Júnior, Josué Ferreira [UNESP]; Klar, Antonio Evaldo [UNESP]; Tanaka, Adriana Aki; Silva, Ilca Puertas de Freitas e [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Putti, Fernando Ferrari [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2014)
The aim of this study was to evaluate the water and salt stress in the germination process of two tomatoes cultivars. The experiment consisted of 16 treatments in a completely randomized design in triple 2 x 2 x 4 factorial design, with two tomatoes cultivars (Santa Adélia and Kátia), two imbibition solutions (PEG6000 and NaCl) and four osmotic potentials (0, -0.2, -0.4 and -0.6 MPa). Each plot was represented by a gerbox with 50 tomatoes seeds. The seeds were remained in contact with the solutions for fourteen days. The germination percentage, emergence rate index, length and dry weight of the seedlings were evaluated. Significant interactions between the factors were deployed. Qualitative factors underwent comparison of means by Tukey test (P < 0.05) and the quantitative analysis by linear regression. According to the results of the study, Santa Adélia cultivar was the most resistant for both situations, hydric and salt stress. The hydric stress was significantly more effective in reducing the results for each variable, except for dry mass. The osmotic potential, from -0.4 Mpa, significantly reduced the germination percentage, index emergency speed and seedlings.

O objetivo deste trabalho foi investigar os efeitos do estresse hídrico e salino no processo germinativo de sementes de duas cultivares de tomate. O experimento, constituído por 16 tratamentos, em delineamento inteiramente casualizado e esquema fatorial triplo 2 x 2 x 4, sendo duas cultivares de tomate (Santa Adélia e Kátia), duas soluções para embebição das sementes (PEG6000 e NaCl) e quatro potenciais osmóticos (0; -0,2; -0,4 e -0,6 MPa). Cada parcela foi representada por uma caixa gerbox com 50 sementes de tomate. Foram avaliados a porcentagem de germinação, índice de velocidade de emergência, comprimento e matéria seca das plântulas. As interações significativas entre os fatores foram desdobradas. Os fatores qualitativos foram submetidos à comparação de médias pelo teste Tukey (P<0,05) e o quantitativo à análise de regressão linear. De acordo com os resultados a cultivar Santa Adélia apresentou melhor resistência, tanto ao estresse hídrico quanto ao salino. O estresse hídrico foi significativamente mais eficiente na redução das variáveis analisadas, com exceção da massa seca. Potenciais osmóticos a partir de -0,4 Mpa reduziram significativamente as variáveis porcentagem de germinação, índice de velocidade emergência e comprimento de plântulas.
Vigor de sementes de tomate submetidos a estresse hídrico ou salino
Keywords: Salinity; Water deficit; Solanum lycopersicum; Salinidade; Déficit hídrico; Solanum lycopersicum